Complete genome sequencing and analysis of Saprospira grandis str. Lewin, a predatory marine bacterium. Issue 1 (January 2012) - Saw, Jimmy; Yuryev, Anton; Kanbe, Masaomi; Hou, Shaobin; Young, Aaron; Aizawa, Shin-Ichi; Alam, Maqsudul
Abstract Saprospira grandis is a coastal marine bacterium that can capture and prey upon other marine bacteria using a mechanism known as 'ixotrophy'. Here, we present the complete genome sequence ofSaprospira grandis str. Lewin isolated from La Jolla beach in San Diego, California. The complete genome sequence comprises a chromosome of 4.35 Mbp and a plasmid of 54.9 Kbp. Genome analysis revealed incomplete pathways for the biosynthesis of nine essential amino acids but presence of a large number of peptidases. The genome encodes multiple copies of sensor globin-coupled rsbR genes thought to be essential for stress response and the presence of such sensor globins inBacteroidetes is unprecedented. A total of 429 spacer sequences within the three CRISPR repeat regions were identified in the genome and this number is the largest among all theBacteroidetes sequenced to date.